Analysis of the Embankment Settlement on Soft Soil Subgrade with a Cement Mixed Pile - Liang Yang; Wenyuan Xu; Keke Li (Advances in Civil Engineering)
The settlement of the widening of soft soil subgrade highways is typically associated with different treatment positions of cement mixed piles. In order to overcome this, in the current paper we employ the finite element method to simulate and analyze the influence of piles under an existing road slope and under an existing subgrade and new embankment on the settlement characteristics of the subgrade and foundation. In particular, we focus on the influence of the pile length and pile spacing on the subgrade and foundation settlements based on a northern high-speed reconstruction and expansion project. The subgrade and foundation soils in the finite element analysis are considered to be homogeneous, continuous, and isotropic elastoplastic materials. The Mohr–Coulomb ideal elastoplastic constitutive model is implemented as the constitutive soil model. The impact of piles under an existing subgrade and new embankment on the settlement is observed to be more significant than that of piles under the existing road slope. Moreover, the subgrade and foundation settlements increase with the pile spacing under the existing road slope and under the existing subgrade and new embankment. More specifically, an increase of the pile spacing from 200% to 400% of the pile diameter is associated with an increase in the maximum settlement of the foundation surface from 1.76 to 1.85 cm (existing road slope) and from 1.44 to 1.96 cm (existing subgrade and new embankment). In addition, the subgrade and foundation settlements decrease for increasing pile lengths under the existing road slope and under the existing subgrade and new embankment, the pile length increases from 4.7 to 9.2 m, and the maximum foundation surface settlement is reduced from 6.2 to 5.52 cm and from 9.73 to 5.43 cm, respectively. The results can provide reference for future subgrade widening projects.